1982
DOI: 10.1073/pnas.79.5.1488
|View full text |Cite
|
Sign up to set email alerts
|

Probable involvement of a glycoconjugate in IMR-32 DNA synthesis: decrease of DNA polymerase alpha 2 activity after tunicamycin treatment.

Abstract: Multiple forms of DNA polymerase a activity (al, a2, and a3) from human neuroblastoma IMR-32 cells untreated or treated with tunicamycin (3 ,ug/ml) were separated by DEAE-cellulose column chromatography. Loss of40-60% ofDNA polymerase a2 activity was observed in tunicamycin-treated cells. Ricin IB, a subunit of intact ricin (Mr, 64,000), was found to be a specific inhibitor of DNA polymerase a2 isolated from control IMR-32 cells. However We report here that tunicamycin (19), which blocks the synthesis of N-ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Reportedly, several lectins such as Concanavalin A bound human catalytic subunit of pol-α (p180), and that ricin from castor beans bound and inhibited pol-α, suggesting that the p180 subunit has carbohydrate chains recognized by these lectins (Bhattacharya et al, 1979;Hsi et al, 1990). Because tunicamycin, which inhibits the glycosylation of protein, has been reported to decrease the activity of pol-α (Bhattacharya & Basu, 1982), it is suggested that the carbohydrate chain on pol-α is important for its activity. However, the detailed roles of carbohydrate chains on p180 subunit have not been elucidated to date.…”
Section: Structure Of Pol-α-primase Complexmentioning
confidence: 99%
“…Reportedly, several lectins such as Concanavalin A bound human catalytic subunit of pol-α (p180), and that ricin from castor beans bound and inhibited pol-α, suggesting that the p180 subunit has carbohydrate chains recognized by these lectins (Bhattacharya et al, 1979;Hsi et al, 1990). Because tunicamycin, which inhibits the glycosylation of protein, has been reported to decrease the activity of pol-α (Bhattacharya & Basu, 1982), it is suggested that the carbohydrate chain on pol-α is important for its activity. However, the detailed roles of carbohydrate chains on p180 subunit have not been elucidated to date.…”
Section: Structure Of Pol-α-primase Complexmentioning
confidence: 99%
“…However, this assay is not capable of appraising many in vivo actions of DNA polymerase I, such as rate, processivity, etc. Various forms of DNA polymerase a (or I) have been isolated from a wide variety of eukaryotic cells (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The complexity of structural variations among different preparations may have been, in part, due to the fragility of the multiprotein polymerase assembly, proteolytic degradation, and lack of suitable assays capable of assessing the in vivo actions of a multifunctional polymerase.…”
Section: Introductionmentioning
confidence: 99%
“…Reportedly, several lectins such as Concanavalin A bound human catalytic subunit of pol-(p180), and that ricin from castor beans bound and inhibited pol-, suggesting that the p180 subunit has carbohydrate chains recognized by these lectins (Bhattacharya et al, 1979;Hsi et al, 1990). Because tunicamycin, which inhibits the glycosylation of protein, has been reported to decrease the activity of pol- (Bhattacharya & Basu, 1982), it is suggested that the carbohydrate chain on pol-is important for its activity. However, the detailed roles of carbohydrate chains on p180 subunit have not been elucidated to date.…”
Section: Structure Of Pol-α-primase Complexmentioning
confidence: 99%